2023
DOI: 10.1371/journal.pdig.0000177
|View full text |Cite
|
Sign up to set email alerts
|

Student peer mentoring: Feasibility and acceptability of mHealth-based tool for alcohol and substance abuse prevention by peer mentors at a university in Kenya

Abstract: Objective The use of mobile health (mHealth)-based interventions for the prevention of alcohol and other psychoactive substances use is an emerging practice for which new evidence is required. This study evaluated the feasibility and acceptability of a mHealth-based peer mentoring tool for early screening, brief intervention, and referral of students who abuse alcohol and other psychoactive substances. It compared the implementation of a mHealth-delivered intervention to the paper-based practice that is the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Evidence-based mhealth interventions can confirm the efficacy of health promotion programs. Several studies have shown the usefulness of mhealth interventions in preventing high-risk behaviors such as smoking, substance abuse, and alcohol consumption (33)(34)(35)(36). Moreover, Moore et al reported that the smoking abstinence rate in these interventions was generally 1.5 times higher than the control group (37).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based mhealth interventions can confirm the efficacy of health promotion programs. Several studies have shown the usefulness of mhealth interventions in preventing high-risk behaviors such as smoking, substance abuse, and alcohol consumption (33)(34)(35)(36). Moreover, Moore et al reported that the smoking abstinence rate in these interventions was generally 1.5 times higher than the control group (37).…”
Section: Discussionmentioning
confidence: 99%
“…• Adequate training with opportunities to practice skills (Murray et al, 2018) • Learning new skills during care provision or training that can be applied to other aspects of their life outside of intervention provision (Giusto et al, 2021;Musyoka et al, 2023) For patients:…”
Section: Qualitative Findings Indicating a Positive Outcome Cmentioning
confidence: 99%